Perkembangan Kognitif dan Implikasinya Terhadap Pembelajaran - Sandy Irsyad (Tafhim Al-'Ilmi, 2023)
Learning is an effort made by educators for students formally or informally in order to learn well. Learning is always related to cognitive, namely as a process that a person undergoes to obtain a change in his behavior as a result of training or experience interacting directly or indirectly with the environment. Cognitive development is a stage of change in humans in terms of managing information, understanding, knowledge and solving a problem. So in learning it is necessary to pay attention to the level of cognitive development of a person. The method used in this research is literature study, collecting information related to this research from books and literature. The results of this study indicate that Piaget's cognitive development theory helps teachers in recognizing, understanding and choosing the right treatment according to the level of cognitive development of students, and Vygotsky's theory helps students in building their social relationships. Keywords: developmental psychology, cognitive, learning